1990
DOI: 10.1097/00004032-199004000-00004
|View full text |Cite
|
Sign up to set email alerts
|

Statistical Analysis of Gamma-emitting Radionuclide Concentrations for Three Fields in Southern Saskatchewan, Canada

Abstract: During 1988, the spatial variability of the natural gamma-emitting radionuclides (238U, 232Th, and 40K) and the artificial radionuclide 137Cs were studied in three near-level unfertilized fields in Saskatchewan, Canada. One field was used as a native (uneroded) control site; the other two sites have been cultivated, one since 1979 and the other since at least the 1940s. The two cultivated sites have been eroded by aeolian processes and tillage practices. Autocorrelation analysis indicated that most of the radi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
0

Year Published

1992
1992
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 43 publications
(14 citation statements)
references
References 24 publications
1
13
0
Order By: Relevance
“…The level of natural variability demonstrated for the Snowy Mountains sites is consistent with that observed by previous studies, which is typically ̴ ̴ 20% in the case of 137 Cs (Kirchner, 2013;Pennock and Appleby, 2003;Sutherland and de Jong, 1990).The intrinsic spatial variability of 210 Pb ex fallout is less well known, but CVs of ̴ 10% (Porto et al, 2009) …”
Section: Radionuclide Reference Inventoriessupporting
confidence: 89%
“…The level of natural variability demonstrated for the Snowy Mountains sites is consistent with that observed by previous studies, which is typically ̴ ̴ 20% in the case of 137 Cs (Kirchner, 2013;Pennock and Appleby, 2003;Sutherland and de Jong, 1990).The intrinsic spatial variability of 210 Pb ex fallout is less well known, but CVs of ̴ 10% (Porto et al, 2009) …”
Section: Radionuclide Reference Inventoriessupporting
confidence: 89%
“…Even though Ulsh et al [21] observed similarly high values (CV=0.40 and 0.41, respectively) for alpine and montane sites in Colorado (USA) as compared to our site, on a meadow in the City of Salzburg (Austria), Lettner et al [22] observed for the spatial variability of Chernobylderived 137 Cs fallout on a 1-ha area a value of only CV=0.21. Similarly, Sutherland and de Jong [23] found for a native grassland a CV=0.18, and McGee et al [24] for the integrated 137 Cs deposition at an upland peat site a value of 0.24. For a recent review, see Sutherland [25].…”
Section: Back-flow Modelmentioning
confidence: 78%
“…Cs (Kirchner, 2013;Pennock and Appleby, 2003;Sutherland and de Jong, 1990 Cs (e.g. Shakhashiro and Mabit, 2009).…”
Section: Spatial Variability Inmentioning
confidence: 99%